Basic researchExtract from Aronia melanocarpa fruits potentiates the inhibition of platelet aggregation in the presence of endothelial cells - Luzak, Boguslawa; Golanski, Jacek; Rozalski, Marek; Krajewska, Urszula; Olas, Beata; Watala, Cezary (Archives of Medical Science, 2010)
Introduction: > Some polyphenolic compounds extracted from Aronia melanocarpa fruits (AM) have been reported to be cardioprotective agents. In this study we evaluated the ability of AM extract to increase the efficacy of human umbilical vein endothelial cells (HUVECs) to inhibit platelet functions in vitro . Material and methods: This study encompasses two models of monitoring platelet reactivity: optical aggregation and platelet degranulation (monitored as the surface CD62P expression) in PRP upon the stimulation with ADP. Results: We observed that only at low concentrations (5 g/ml) did AM extract significantly improve antiplatelet action of HUVECs towards ADP-activated platelets in the aggregation test. Conclusions: It is concluded that the potentiating effect of AM extract on the endothelial cell-mediated inhibition of platelet aggregation clearly depends on the used concentrations of Aronia-derived active compounds. Therefore, despite these encouraging preliminary outcomes on the beneficial effects of AM extract polyphenols, more profound dose-effect studies should certainly be considered before the implementation of Aronia-originating compounds in antiplatelet therapy and the prevention of cardiovascular diseases.